(untitled) - Luttgens, Jason T. (New York, 2014)
This new edition is chock-full of updates about tools and techniques as well as real-world scenarios reflecting today's most common types of incidents. Specific, detailed advice covers all aspects of incident investigation and handling, with an emphasis on forensics. Special features highlight important tips for security practitioners: the Law Enforcement feature that appears throughout all chapters provides advice on when and how law enforcement must be informed; the What Can Happen feature shows how badly certain scenarios could turn out (with non-action or wrong-action) and why; the Where to Look feature guides you through the fastest routes to key evidence; and the Eye Witness feature details relevant real-world cases for context and urgency
CT297
Keywords: Computer security,Computer crimes,Bảo mật máy tính,Tội phạm máy tính; Investigation.,Cuộc điều tra